Fostering comprehension in English classes : beyond the basics - Philippot, Raymond; Graves, Michael F. (New York, NY : Guilford Press, 2009)
This valuable, research-based guide gives middle and secondary English teachers the tools they need to improve the comprehension skills of all their students. Core chapters explain specific practices for fostering learning from texts; leading students to a thorough, lasting understanding of subject matter; nurturing meaningful responses to literature; explicitly teaching comprehension strategies; and engaging students in higher-order thinking. An additional chapter highlights vocabulary instruction. Throughout, attention is given to building comprehension skills in a diverse range of students, from high achievers to struggling readers and English language learners. A wealth of hands-on materials are featured, including lesson plans, scaffolded reading experiences, and a richly detailed example of a teaching unit that shows how all facets of comprehension instruction can be brought together in the classroom. - Publisher.
Our take on adolescent literacy -- Fostering learning from text -- Teaching for understanding -- Fostering responses to literature -- Teaching comprehension strategies -- Teaching higher-order thinking skills -- Vocabulary instruction in English classes -- Comprehension in context.
Includes bibliographical references (p. 213-222) and index.
Keywords: Reading comprehension; Reading (Middle school); Reading (Secondary); Englischunterricht; Leseverstehen